Comparison of bilateral pectoral nerve block 2 and local anesthetic infiltration for pain control in cardiac surgery (Annals of Medical Research, 2022)
Aim: We aimed to compare the effect on postoperative pain of pre-emptive bilateral Pectoral Nerve Block 2 by ultrasound with local anesthetic infiltration on the sternotomy line and drain insertion points in cardiac surgery.Materials and Methods: The study included 40 patients with open heart surgery under general anesthesia aged over 18 years. Patients were randomly divided into 2 groups. Group 1(bilateral Pectoral Nerve Block 2 (PECS 2) performed with ultrasound) and Group 2 (local anesthesia infiltration). Patients had intraoperative and postoperative opioid consumption amounts, duration on ventilator, visual analog scale (VAS) scores when moving (cough) and at rest, inspiratory flow rates and hospitalization duration recorded.Results: Group 1 was identified to have lower intraoperative and postoperative opioid consumption amounts (p
Keywords: Cardiac surgery; local infiltration; opioid consumption; pain control; pectoral nerve block